Characteristics of epidermis of leaves and confirmation of stomatal complexes and appendages of species of plants of the families Chenopodiaceae and Compositae (Asteraceae) grown wild in Karbala province. (Journal of the College of Basic Education, 2022)
The current study dealt with the stomata complexes and the study of leaf cuticle characteristics for several species of my family. The diversity of shapes and types of stomata complexes for the types of plants under study, but the majority of them were Aisocytic, Anomocytic and Anomtetracytic, except in the type Haloxylon salicornicum which has a Brachyparacytic stomatal complex for the upper surface only.